Risk assessment method of FPSO towing operation based on cloud model - CHEN Jinming; CHEN Hao; LIU Guofeng; CHEN Haicheng (You-qi chuyun, 2022)
In order to prevent the safety and environment accidents during the towing process of Floating Production Storage and Offloading(FPSO) system, the potential risk factors in the towing process were identified by classification, the risk evaluation indicator system of FPSO towing operation was constructed and a comprehensive risk evaluation method of FPSO towering operation based on cloud model was developed. To deal with the fuzziness and randomness in subjective evaluation, a cloud model construction method was proposed for the standard cloud and risk level reference cloud for the evaluation indicators of risk factors. Meanwhile, the domain expert weight was gained by introducing in the entropy weight method, and the comprehensive evaluation cloud of risk factors was obtained with the cloud model fusion method.Besides, the risk evaluation cloud for single-factor was obtained with consideration to the influence on risk probability and consequence, and the comprehensive evaluation matrix was gotten by calculating the proximity of risk cloud to the reference cloud. Further, the weight vector of risk evaluation indicator was acquired with the Analytic Hierarchy Process(AHP) method, and thus the fuzzy comprehensive evaluation was performed for FPSO towing operation. Finally, the risk level was determined on the maximum membership principle. Generally, the risk level of towing operation was evaluated and prejudged effectively by applying this method to the risk evaluation of FPSO towing project in an oilfield, which verifies the accuracy of the method, capable of providing guidance for decision-making on safety of FPSO towing operations.